Design of 1 435/1 420 mm EMUs Gauge Changeable Wheelset and Its Gauge Changeable Ground Equipment - XU Zhongxuan; LIU Xiaoyan; HUANG Yunhua; WANG Yutao (机车电传动)
Combined with the railway’s current situation of China and neighbors, and according to the technical parameters of standard EMUs bogies, a scheme of EMUs gauge changeable wheelset and its gauge changeable ground equipment was put forward which was used on gauge for 1 435 mm and 1 520 mm, and the process of its gauge changeable was introduced. The analysis showed that the scheme could realize automatic conversion of wheelset inner distance.